The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acs.est.2c05228
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Methane Oxidation by Nitrogen Availability in Arctic Tundra Soils

Abstract: CH4 emission in the Arctic has large uncertainty due to the lack of mechanistic understanding of the processes. CH4 oxidation in Arctic soil plays a critical role in the process, whereby removal of up to 90% of CH4 produced in soils by methanotrophs can occur before it reaches the atmosphere. Previous studies have reported on the importance of rising temperatures in CH4 oxidation, but because the Arctic is typically an N-limited system, fewer studies on the effects of inorganic nitrogen (N) have been reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…However, no such enrichment of 13 C-labeled metabolites was observed in the red soil, where methanotrophs were predominantly composed of (over 90%) type II methanotrophs. Previous studies have reported that type II methanotrophs, including Methylocystis and Methylosinus , were less tolerant to high N concentration 47 , 48 . Therefore, the effects of NO 3 − on methanotrophs may exert confounding effects on the coupling between CH 4 oxidation and denitrification.…”
Section: Discussionmentioning
confidence: 89%
“…However, no such enrichment of 13 C-labeled metabolites was observed in the red soil, where methanotrophs were predominantly composed of (over 90%) type II methanotrophs. Previous studies have reported that type II methanotrophs, including Methylocystis and Methylosinus , were less tolerant to high N concentration 47 , 48 . Therefore, the effects of NO 3 − on methanotrophs may exert confounding effects on the coupling between CH 4 oxidation and denitrification.…”
Section: Discussionmentioning
confidence: 89%
“…Natural gas has been widely used as an energy source in vehicles or power plants. [1][2][3] Catalytic methane (CH 4 ) as a greenhouse gas is the main component of natural gas, which causes serious harm to the environment. 4,5 In response to the premise that the country strongly advocates carbon neutrality, it is urgent to effectively eliminate CH 4 emission.…”
Section: Introductionmentioning
confidence: 99%